Pengaruh Sosialisasi Perpajakan, Insentif Pajak, dan Digitalisasi Layanan terhadap Tingkat Kepatuhan Wajib Pajak Bumi dan Bangunan Perdesaan Perkotaan pada Unit Pelayanan Pemungutan Pajak Daerah Kecamatan Jagakarsa - Widyarini, Estie; As'ad, Muhammad (Jurnal Pajak Vokasi (JUPASI), 2024)
The purpose of this research is to identify the influence of tax socialization, tax incentive, and tax digitalization on rural and urban land and building taxpayer compliance level at The Regional Tax Collection Service Unit, Jagakarsa subdistrict. This research is a descriptive statistical research with quantitative approach. Population in this research is the rural and urban land and building taxpayers at The Regional Tax Collection Service Unit, Jagakarsa subdistrict. 100 respondents as sample is taken by using simple random sampling method by Slovin. Data is collected by using questionnaire and processed by using SPSS statistics 26. The result shows that tax socialization has influence on taxpayer compliance as big as 62.6%, tax incentive has influence on taxpayer compliance as big as 52%, and tax digitalization has influence on taxpayer compliance as big as 53.2%, making socialization, tax incentive, and tax digitalization have significant influence on rural and urban land and building taxpayer compliance at The Regional Tax Collection Unit, Jagakarsa subdistrict. Tax socialization, tax incentive, and tax digitalization, simultaneously, influence taxpayers as big as of 72.6% where 27.4% is influenced by other variables which are not included in this research